Factors Providing Independent Cognitive Activity in Teaching Engineering Computer Graphics - Tashimov Nurlan Erpolotovich (Genius Publishing Group, 2022)
The article proposes to consider the construction of second-order curves as a crosssection of a circular cone with planes of different positions and the origin of foci as a result of the point of contact of a sphere inscribed inside a triangle composed of extreme generators and a secant plane. This approach of presenting the material, which is absent in textbooks, according to the opinion and experience of the authors, contributes to the activation of cognitive activity of students.
Keywords: Engineering computer graphics; independent cognition; quality of education; graphic education